MENGUNGKAP SIFAT-SIFAT TERPUJI MANUSIA DALAM CERITA RAKYAT SASAK: SUATU KAJIAN TEMATIS - Lalu Fakihuddin (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2014)
This study describes ideal characters reflected in Sasaknese Folklore (Cerita Rakyat Sasak). The design of this study is qualitative implementing descriptive-interpretive techniques. Sources of the data of this study were sequences of the Folklore representing ideal characters of human beings.  Specifically, this study used hermeneutic approach, an approach from which indepth analysis of a text is applied.  Data analysis referred to perspective-constructive that focused on intensity, determined categories, and target of the expected result.  The study revealed that Sasakne Folklore is one of the oral folklore reflecting high human values.  The good characters included religious, work hard, patient, high responsibility, mutual-consultative, and loyal.